RNA from the yeast transposable element Ty1 has both ends in the direct repeats, a structure similar to retrovirus RNA. - Elder, R T (1983)
The RNA homologous to the yeast transposable element Ty1 is one of the more abundant poly(A)+ RNAs in many strains of the yeast Saccharomyces cerevisiae. The 5' and 3' ends of Ty1 RNA have been determined from analysis of cDNA. The 5' end is 245 bases into the left delta sequence measured from the left side of the Ty1 element. The delta sequence is a direct repeat of about 340 base pairs present at each end of the Ty1 element. The Ty1 transcription includes 93-97 bases of the left delta sequence and continues through the entire internal portion of the element and through about 295 bases of the right delta sequence before reaching the 3' end located 38-46 bases from the right side of the right delta sequence. Because the delta sequences present at each end of a single Ty1 element have identical or very similar DNA sequences, these end points for Ty1 RNA raise several questions about the expression of Ty1 elements. First, what are the initiation and termination signals, because the Ty1 transcript must read through a DNA sequence that is identical to the 3' end at about 50 bases from the 5' end? Second, why is the direction of transcription of the Ty1 element opposite to that of genes that are overexpressed after the insertion of a Ty1 element? Third, because the Ty1 RNA itself has direct repeats of about 45 bases, a structure analogous to retrovirus RNAs, is the Ty1 RNA an intermediate in the transposition of Ty1?